Parents' and teachers' attitudes to and experiences of the implementation of COVID-19 preventive measures in primary and secondary schools following reopening of schools in autumn 2020: a descriptive cross-sectional survey. Issue 9 (28th September 2022) - Amin-Chowdhury, Zahin; Bertran, Marta; Kall, Meaghan; Ireland, Georgina; Aiano, Felicity; Powell, Annabel; Jones, Samuel E; Brent, Andrew J; Brent, Bernadette E; Baawuah, Frances; Okike, Ifeanychukwu; Beckmann, Joanne; et al.
Abstract : Objective: To assess implementation and ease of implementation of control measures in schools as reported by staff and parents. Design: A descriptive cross-sectional survey. Setting: Staff and parents/guardians of the 132 primary schools and 19 secondary schools participating in COVID-19 surveillance in school kids (sKIDs and sKIDsPLUS Studies). Main outcome measure: Prevalence of control measures implemented in schools in autumn 2020, parental and staff perception of ease of implementation. Results: In total, 56 of 151 (37%) schools participated in this study, with 1953 parents and 986 staff members completing the questionnaire. Most common measures implemented by schools included regular hand cleaning for students (52 of 56, 93%) and staff (70 of 73, 96%), as reported by parents and staff, respectively, and was among the easiest to implement at all times for students (57%) and even more so, for staff (78%). Maintaining 2-metre distancing was less commonly reported for students (24%–51%) as it was for staff (81%–84%), but was one of the most difficult to follow at all times for students (25%) and staff (16%) alike. Some measures were more commonly reported by primary school compared to secondary school parents, including keeping students within the same small groups (28 of 41, 68% vs 8 of 15, 53%), ensuring the same teacher for classes (29 of 41, 71% vs 6 of 15, 40%). On the other hand, wearing a face covering while at school was reported by three-quarters of secondary school parents compared with only parents of 4 of 41 (10%) primary schools. Other measures such as student temperature checks (5%–13%) and advising staff work from home if otherwise healthy (7%–15%) were rarely reported. Conclusions: Variable implementation of infection control measures was reported, with some easier to implement (hand hygiene) than others (physical distancing).